Analyzing different acetyl co-a metabolizing enzymes as potential drug targets against mycobacterium tuberculosis - Akhtar, Shamim; Singh, Sheetal; Kumar, Santosh; Sarkar, Dhiman (British Microbiology Research Journal, 2015)
Mycobacterium tuberculosis, the causative agent of tuberculosis, is responsible for the deaths of million people around the globe. The scenario is worse than ever due to the emergence of drug resistant strains which are widely spread throughout the globe in much faster ways. To control this worst situation, we need to speed up the search for novel drugs which can specifically kill drug resistant bacteria in collaborative ways amongst academic, clinician and industry. Among different metabolic pathways, fatty acid synthesis pathway has always been a very attractive area for the drug target because of its crucial role during the infection and further in long term survival of pathogen inside the human host. In this review article, we analyzed the role of important and crucial enzymes, which are responsible for the influx and efflux of acetyl co-A substrate, a central hub of metabolites, as potential drug targets against M. tuberculosis.